A comparative study on the reaction mechanisms of Cp2MH2 (M = Cr, Mo, W) with HBF4. (28th January 2019) - Xu, Xia; Sun, Zheng; Meng, Lingpeng; Zheng, Shijun; Li, Xiaoyan
Abstract : The reaction mechanisms of group 6 transition metal dihydride complexes, Cp2 MH2 (M = Cr, Mo, and W), and HBF4 were studied using M06‐L density functional theory. The chemical bond changes along the reaction pathway are analyzed by the topological analysis of electron density. The calculated results show that the interactions between the H atom of HBF4 and Cp2 MH2 are stronger than those between Cp2 MH2 and BF3 ; additionally, due to the low energy barriers in the subsequent reaction, all the title reactions can occur easily, and the yield rates of the Cp2 MH2  + HBF4 reactions are high. For M = Cr and Mo, the [Cp2 MH3 ] + in the product Cp2 MH3 ·BF4 is in the nonclassic dihydrogen‐hydride form ([Cp2 M( η 2 ‐H2 )H] + ). [Cp2 CrH3 ] + and [Cp2 MoH3 ] + are unstable, and H2 can be easily liberated from them. For M = W, the final product is Cp2 WH3 ·BF4, and [Cp2 WH3 ] + is stable in the classic trihydride form. Abstract : The different reaction mechanisms of Cp2 MH2 + HBF4 and the different stable formations of [Cp2 MH3 ] + (M=Cr, Mo, W) were illustrated.